2015
DOI: 10.1002/jbm.a.35429
|View full text |Cite
|
Sign up to set email alerts
|

In vitro interactions of blood, platelet, and fibroblast with biodegradable magnesium‐zinc‐strontium alloys

Abstract: Magnesium (Mg) alloy is an attractive class of metallic biomaterial for cardiovascular applications due to its biodegradability and mechanical properties. In this study, we investigated the degradation in blood, thrombogenicity, and cytocompatibility of Magnesium-Zinc-Strontium (Mg-Zn-Sr) alloys, specifically four Mg-4 wt % Zn-xSr (x = 0.15, 0.5, 1, and 1.5 wt %) alloys, together with pure Mg control and relevant reference materials for cardiovascular applications. Human whole blood and platelet rich plasma (P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
18
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 20 publications
(19 citation statements)
references
References 29 publications
1
18
0
Order By: Relevance
“…The results of this study suggested that media alkalinity induced more dramatic effects on cellular functions than [Mg 2+ ] from the degradation of Mg-based materials, which were in agreement with previous studies for bone marrow derived mesenchymal stromal cells (BMSCs) [29,76], UMR-106 rat osteosarcoma [77], and hESCs [47]. Overall, the cytocompatibility results of Mg-Zn-Sr alloys with HUVECs reported in this study were in general agreement with previous in vitro studies with hESCs [27] and fibroblasts [28,53,67]. …”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations
“…The results of this study suggested that media alkalinity induced more dramatic effects on cellular functions than [Mg 2+ ] from the degradation of Mg-based materials, which were in agreement with previous studies for bone marrow derived mesenchymal stromal cells (BMSCs) [29,76], UMR-106 rat osteosarcoma [77], and hESCs [47]. Overall, the cytocompatibility results of Mg-Zn-Sr alloys with HUVECs reported in this study were in general agreement with previous in vitro studies with hESCs [27] and fibroblasts [28,53,67]. …”
Section: Discussionsupporting
confidence: 92%
“…Other ternary polycrystalline Mg-Zn-X alloys, including X = Al [40,57–59], Ca [29,60,61], Yttrium [62], Zirconium [63], Mn [64,65], Si [65], and Selenium and Copper (Cu) [66], exhibited solution strengthening and β-phase-mediated corrosion. To highlight the significance and novelty of this study in comparison with the state-of-the-art, a thorough review on the history and current development of as-cast crystalline Mg-Zn-Sr ternary alloys is summarized in Table 2 [2628,5256,67]. …”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…ions) can be gradually reused as required mineral nutrients for body supplement. Several studies have investigated the effects of Mg ions on in vitro cell behavior, and reported the Mg ion-induced promoting effect on the proliferation rate of osteoblasts, endothelial cells and fibroblasts [12][13][14]. Furthermore, Mg and other biocompatible metal ions (e.g.…”
Section: Introductionmentioning
confidence: 98%